A Conceptual Model on Integrating Supply Chain Operations Reference (SCOR) into Disaster Response Service Supply Chain FMEA - Agung Sutrisno; Benny L. Maluegha; Jan Soukotta (International Journal of Innovation in Enterprise System, 2018)
Becoming country prone to the occurrence of natural disasters, determination on risk variables affecting successful operation of disaster response service supply chain using supply chain FMEA (Failure Mode and Effect Analysis) is undeniably important to support successfulness of humanitarian operation. However, scientific studies concerning on integrating SCOR into Risk evaluation of disaster response supply chain is rarely found in references. To response such gap, this paper presents a conceptual model on integrating disaster response supply chain FMEA with Supply Chain Operational Reference (SCOR) to determine a conceptual risk-based performance evaluation model in disaster response supply chain. A framework on integrating Service Supply Chain FMEA with SCOR is presented coupled with a decision support model for evaluating criticality of risk-based performance index and followed with discussions and new opportunity for further investigations. Keywords—Service Supply Chain, FMEA, SCOR, Disaster Response, Risk.